ANALISIS PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DANA BAGI HASIL PAJAK, FLYPAPER EFFECT TERHADAP KAPASITAS FISKAL DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA (Lembaga Pengembangan Kinerja Dosen, 2022)
Increasing local government PAD needs to pay attention to posts that are the main regional revenues. This is to increase Fiscal Capacity in realizing regional independence. This study aims to determine the effect of Regional Tax (PD), Regional Retribution (RD), Revenue Sharing Tax Revenue (DBHP) and Flypaper effect (FE) on Fiscal Capacity (KF). This study uses quantitative analysis techniques, and the population of this study is the Special Region of Yogyakarta while the sampling technique chosen is purposive sampling with a research sample of 5 districts/cities in the province of DIY. The data that has been collected was analyzed using data analysis which first tested the classical assumptions before testing the hypothesis. Hypothesis testing in this study using multiple regression analysis with t test, f test, and the coefficient of determination. The results of this study indicate that Local Tax (PD) has a significant negative effect, Regional Retribution (RD) has a significant positive effect, and the Flypaper effect (FE) has a significant negative effect on Fiscal Capacity (KF). Meanwhile, the Tax Revenue Sharing Fund (DBHP) has no significant effect on Fiscal Capacity (KF).